(untitled) (Journal of Educational Sciences, 2022)
The article deals with the problem of training a foreign language teacher for industry purposes. The term “professional language” is defined by analyzing the scientific works of well-known researchers and linguists. The importance of mastering the metalanguage of communication for the aviation sector is emphasized. The concept of “aviation language” is given and the requirements for proficiency in the English language of aviation radiotelephone communication and its impact on flight safety are prescribed. The article also analyzes the requirements of ICAO (International Civil Aviation Organization). Knowledge of aviation English is determined using 6 levels for conducting effective communication between aviation services, the pilot and the air traffic controller. The significance of the results of the integration of the aviator’s metalanguage skills, which make up the communicative competence, is noted. The conditions for different levels of language proficiency are identified and professional areas of application in various situations related to the context of communication are described. The concept of “contextual learning” and its role as a model of the future professional activity of a specialist is defined. The types of exercises for improving the level of language competence of the student are proposed, which are built according to the requirements of contextual learning, where participants enter into professional communication to solve the tasks set. Key words: professional language, aviation language, ICAO, contextual learning, communicative competence.